2013
DOI: 10.1038/bjc.2013.132
|View full text |Cite
|
Sign up to set email alerts
|

A short-term colorectal cancer sphere culture as a relevant tool for human cancer biology investigation

Abstract: Background:Ex vivo colospheres have been previously characterised as a colorectal cancer (CRC) well-rounded multicellular model, exclusively formed by carcinoma cells, and derived from fresh CRC tissue after mechanical dissociation. The ability to form colospheres was correlated with tumour aggressiveness. Their three-dimensional conformation prompted us to further investigate their potential interest as a preclinical cancer tool.Methods:Patient-derived CRC xenografts were used to produce numerous colospheres.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…The advantages for cancer cells included convenience source, limitless passages, and easily clutured in a large-scale. Nonetheless, the findings of previous studies concluded from cancer cell models did not reflect the real responsive mechanisms during CRC chemotherapy [23,24]. The discrepancy between cancer cell lines and cancer tissues is partially resulted from variation during continuous passages [25].…”
Section: Discussionmentioning
confidence: 86%
“…The advantages for cancer cells included convenience source, limitless passages, and easily clutured in a large-scale. Nonetheless, the findings of previous studies concluded from cancer cell models did not reflect the real responsive mechanisms during CRC chemotherapy [23,24]. The discrepancy between cancer cell lines and cancer tissues is partially resulted from variation during continuous passages [25].…”
Section: Discussionmentioning
confidence: 86%
“…Herein, PDXs derived from NSCLC brain metastases gave rise to numerous tumor spheres in a few days after mechanical dissociation ex vivo in a reproducible manner, whereas PDXs from NSCLC primary tumor demonstrated poor viability and sphereforming ability in vitro. In previous study, the ability to form tumor spheres was also correlated with tumor aggressiveness, and the chemosensitivity of tumor spheres was similar to that of the in vivo original xenografts (50). Therefore, ex vivo tumor spheres would be one of the potential preclinical tools for the validation of new drugs in a setting that more closely resembles patients' tumors but also for the investigation of patient-tailored therapeutics with high-throughput drug screen.…”
Section: Discussionmentioning
confidence: 89%
“…However, afatinib reportedly exhibits therapeutic effects on patients with NSCLC with EGFR exon-20 duplication (insertion) mutations (29), which was reproduced in vitro in this study. In addition, tivantinib, an MET-targeted agent, showed a similar IC 50 (270 nmol/L) for the proliferation of LC-MBT-15 cells to that of afatinib. Interestingly, the sensitivity was correlated with decreased phosphorylation of ERK regardless of the primary therapeutic targets (Fig.…”
Section: Preservation Of the Parental Nsclcs' Biologic Characteristicmentioning
confidence: 87%
See 2 more Smart Citations